Genomic methods for tracking bacterial pathogens for clinical and public health benefit: case studies - Maiden, Martin C.J.; Rodrigues, Charlene M. C. (Henry Stewart Talks, 2022)
Genomics, Mycobacterium tuberculosis, Infection control and outbreaks, Surveillance, Tracking infectious diseases, Non-typhoidal Salmonella, Neisseria meningitidis, Klebsiella pneumonia